On Behalf of the Family Farm : Iowa Farm Women's Activism since 1945 - Devine, Jenny Barker (Book collections on Project MUSE., 2013)
This book traces the development of women's activism and agrarian feminisms in the Midwest after 1945, as farm women's lives were being transformed by the realities of modern agriculture. The author demonstrates that in an era when technology, depopulation, and rapid economic change dramatically altered rural life, midwestern women met these challenges with their own feminine vision of farm life. Their "agrarian feminisms" offered an alternative to, but not necessarily a rejection of, second-wave feminism.